Leading Inclusion drive change your employees can see and feel - Cox, Gena. (Page Two, 2022)
Why are workplace diversity, equity, and inclusion (DEI) efforts often disappointing? Organizational psychologist and executive coach Gena Cox asserts that although human variation is normal, true inclusion that embraces these variations remains elusive in the workplace. Leading Inclusion, a "how-to-be" book, educates, challenges, and empowers executives and business owners to lead inclusion from the top of the organization.
Includes index
Keywords: Leading